Preparation of a restricted access material–macroporous hybrid monolithic column – for on-line solid-phase extraction of the sulfonamides residues from honey. Issue 4 (19th January 2015) - Lv, Yun-Kai; Guo, Zhi-Yong; Wang, Jin-Zhi; Guo, Meng-Meng; Yu, Lin-Kang; Fang, Hui
Abstract : A novel RAM–HMC with superior enrichment and clean-up efficiency was prepared by an in situ method in a stainless-steel column, and used as a pre-column for on-line solid-phase extraction of sulfonamides residues from honey. Abstract : A novel restricted access material–hybrid monolithic column (RAM–HMC) was prepared by the sol–gel method in a stainless-steel column and an in situ modification method in the through-hole of the HMC. The hydrophobic HMC was prepared by the acid-catalytic reaction of methyltrimethoxysilane and tetraethoxysilane. The hydrophilic structures were formed on the through-hole surface of the HMC by grafting 3-(2, 3-epoxypropoxy) propyltrimethoxysilane. The synthetic conditions were optimized for obtaining the uniform microchannel and the stable skeleton structure. The chemical group, morphology, dynamic adsorption capacity, swelling, and hydrophilic and hydrophobic characteristics of the monolithic column were characterized by the IR, SEM, dynamic binding, solvent adsorption, chromatographic analysis of serum proteins and benzene series, respectively. When the RAM–HMC was used as a precolumn for the on-line extraction of sulfonamide residues from the honey samples, an enrichment factor of 16.9 and a better sample clean-up effect were obtained under the optimized conditions. The average recoveries of three sulfonamide antibiotics from honey spiked at 0.05, 0.1 and 0.2 mg kg −1 were in the range of 73.50–105.80% with a precision of 2.25–5.32%. The limits of detection and quantitation of the proposed method ranged from 6.9–14.6 μg kg −1 and 23.0–48.2 μg kg −1, respectively. The proposed method was successfully applied to the on-line extraction and determination of sulfonamide antibiotics in the honey sample.